RENCANA STRATEGIS PENANGANAN KETIMPANGAN FISKAL (FISCAL IMBALANCE) DI REGIONAL PAPUA BARAT - Al-Firdaus, Farid; Dendy Rizaldy Rachman (Polytechnic of State Finance STAN, 2024)
The Regional Transfer Funds for West Papua, allocated for over 15 years, have not significantly reduced poverty levels nor improved the local Human Development Index. This study aims to analyze this situation and propose solutions through the enhancement of quality spending to achieve the local welfare vision outlined in the Long-Term Regional Development Plan of West Papua Province for 2006-2025. Fiscal decentralization is intended to provide public services with better priorities and preferences; however, fiscal imbalances may occur due to dependency on central transfers and limited local taxation capacity. A qualitative method was employed to address the complexity of these issues through literature reviews, interviews, and focus group discussions. Triangulated findings from these sources highlight the strengths, weaknesses, opportunities, and threats faced by the local government in addressing fiscal imbalances. Strategic issues were identified, encompassing organizational goal attainment, resources, management, and the collaboration capabilities of local governments. The Papua Steering Agency is expected to guide local governments in internalizing the community welfare vision, optimizing civil servant development spending, and evaluating financial management regulations as well as the readiness of governance systems to implement the regional development acceleration master plan.